Staff’s Perspectives of Credit Department toward Debt Restructuring Policy, Bank of Lao. PDR. Case study: Commercial Banks in Luang Prabang - KHOUNKHAM , Sangthong; CHANTHAVONE , Thongphanh; PHOUNNALY, phaivanh; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The current situation of the world economy and the economy of Lao PDR is now unstable which affects businesses and leads to problems and challenges especially, business competitors, natural disasters and the spread of Virus Covid-19. As a result, businesses have taken out loans from commercial banks, which is hard to pay off their debts. The study on staff’s perspectives of Credit Department toward debt restructuring policy, Bank of Lao PDR (BoL) expects to create the standardize of debt restructuring policy for commercial banks. The tool deployed in this study was quantitative research based on the survey from Commercial Bank’s Credit Officers in Luang Prabang by questioning and surveying 55 samples. The data was analyzed by the descriptive statistics. Perspectives of commercial bank credit officers on debt restructuring of BoL mostly agree with high level, The debt restructing is an important lesson for: 1) solving credit problems, 2) careful offering credit, and 3) keeping close relation between the commercial bank and clients. These can help the clients pay off the debt in the future and help reduce debt arrears. Most disagreements help to reduce the issue of non-performing loan (NPL). The practical understanding of commercial bank credit officers on credit restructuring principles of BoL mostly agree in high level in terms of transforming short-term debt to long term debt, reducing interest rate, extending loan repayment period, and reducing principal or interest. The practical feasibility of commercial bank credit officers on credit restructuring principles of BoL mostly agree with medium level in terms of transferring assets into collateral, extending the duration of the loan, and transforming short-term debt to long term debt. The practical difficulties of commercial bank officers on debt restructuring principles of BoL are mainly transferring debt with the contractual obligation to repurchase, transferring non-collateral for debt repayment, reducing interest rate and changing debt into principal.